1985
DOI: 10.5144/0256-4947.1985.79
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy for Childhood Acute Lymphocytic Leukemia

Abstract: This study for previously untreated childhood acute lymphocytic leukemia, conducted from April 1981 to November 1983, included 91 patients divided in two distinct groups, according to clinical and laboratory features at diagnosis. The standard risk group consisted of 64 patients, while the high risk group had 27 patients. The therapy differed according to the risk group. The following are the results for the standard risk and high risk groups, respectively: (1) early death rate, 7.8% and 26%; (2) induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…1 These figures, mainly for the high-risk group, were very high and indicated that the effectiveness of prevention of central nervous system leukemia, according to the designs of the protocol, was inadequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These figures, mainly for the high-risk group, were very high and indicated that the effectiveness of prevention of central nervous system leukemia, according to the designs of the protocol, was inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…1 The complete remission rate obtained was 97% (57 out of 59 patients) for the standard-risk group, and 90% (18 out of 20 patients) for the high-risk group.…”
Section: Introductionmentioning
confidence: 86%
“…For example, Middle East Childhood Cancer Alliance (MECCA) and the Saudi Arabian Pediatric Hematology/Oncology Society (SAPHOS) have conducted collaborative studies prospectively as well as retrospectively to collect data, which would serve as the basis for the subsequent clinical studies. Many single center/institutional studies have also been conducted to assess patients' characteristics and outcome of childhood ALL in KSA and to compare survival with respect to developed countries (Al-Nasser et al, 2008;Aur et al, 1985;Khalil et al, 1994). The present study is another addition to the efforts towards improving outcome of childhood ALL in KSA.…”
Section: Improved Outcomes Of Childhood Acute Lymphoblastic Leukemia:mentioning
confidence: 99%
“…Successful bone marrow transplantation with a combination of cyclophosphamide and total body irradiation as a conditioning regimen was first reported in the 1970s. [3] occurrence of engraftment, acute and chronic graftversus-host disease with BU/CY, but had higher rates of cataract, interstitial pneumonitis, later growth or developmental problems.…”
mentioning
confidence: 95%